Targeted Thrombospondin-1 Expression in Ocular Vascular Development and Neovascularization - Sorenson, Christine M.; Wang, Shoujian; Darjatmoko, Soesiawati R.; Gurel, Zafer; Liu, Bo; Sheibani, Nader (Frontiers in Cell and Developmental Biology, 2021)
Tight regulation of positive and negative regulators of angiogenesis is essential, particularly in the eye where their dysregulation can lead to vision loss. Thrombospondin-1 (TSP1) is a matricellular protein that negatively regulates angiogenesis and inflammation in the eye. It aids ocular vascular homeostasis such that its loss contributes to increased retinal vascular density and pathologic ocular neovascularization. Our previous studies demonstrated that mice globally lacking TSP1 expression had increased retinal vascular density, decreased hyperoxia-induced retinal vessel loss, and increased choroidal neovascularization. Here we determined the impact to the ocular vasculature of endothelial cell, pericyte, or astrocyte loss of TSP1 expression. Only lack of TSP1 expression in endothelial cells was sufficient to increase choroidal neovascularization with mice lacking expression in pericytes or astrocytes not demonstrating a significant impact. Although the global TSP1 knockout mice demonstrated increased retinal vascular density, individual cell type loss of TSP1 resulted in decreased retinal endothelial cell numbers before and/or after vascular maturation in a cell type specific fashion. Retinas from mice lacking TSP1 expression in endothelial cells, pericytes or astrocytes were not protected from retinal vessel regression in response to hyperoxia as we previously observed in the global knockout. Thus, modulation of TSP1 expression in individual cell types demonstrates a response that is unique to the role TSP1 plays in that cell type of interest, and their coordinated activity is critical for vision.